An Examination of the Links Between Organizational Social Capital and Employee Well-Being: Focusing on the Mediating Role of Quality of Work Life. (March 2021) - Ko, Myeong Chul
Although organizational social capital (OSC) is widely considered a potential resource for improving organizational performance, extensive research has paid limited attention to how employee well-being may be a positive outcome of OSC. Drawing on social exchange theory, need satisfaction, and spillover approaches, this study explores the effects of OSC on subjective well-being (SWB) through quality of work life (QWL) and job-related outcomes, such as organizational commitment and turnover intention. Using survey data obtained from public employees in South Korea, the results show that QWL mediates not only the association between OSC and organizational commitment but also the relationship between OSC and SWB. These findings highlight the importance of OSC as an intangible asset that can generate both organizational outcomes and employee well-being. In practice, these findings also imply that organizational resources and work environments should favorably respond to employees' human needs to ensure improved employee well-being.